The Effect of Digital Promotion and Brand Awareness on Purchasing Decisions on Scarlett Whitening Skincare Products (Study on TikTok Shop User Students ar FEB UNM) - Johnson, Nur Atifah Septira; Amin, Andi Mustika; Haeruddin, Muhammad Ilham Wardhana; Ruma, Zainal; Hasdiansa, Ilma Wulansari (The Graduate School of Sahid University, 2024)
In the digital era with the internet that is increasingly developing like today with the sophistication of this technology, it has a major effect on consumer behavior. Digital promotion has become one of the main strategies in marketing efforts to reach consumers who are increasingly connected online. Meanwhile, brand awareness remains an important aspect in shaping consumer perceptions of brands and products. The purpose of this study is to ascertain how Scarlett Whitening product purchasing decisions are influenced by digital promotion and brand awareness among students at Makassar State University's Faculty of Economics and Business. The study's population consisted of 70 enrolled students from Makassar State University's 2020 class in the Faculty of Economics and Business. A questionnaire was used to obtain the data. Multiple linear regression analysis utilizing the Statistical Product and Service Solution (SPSS) is the data analysis method employed. The study's findings suggest that digital promotion partially has a positive and significant effect on Purchasing Decisions. Brand Awareness partially has a positive and significant effect on Purchasing Decisions. Meanwhile Digital Promotion and Brand Awareness simultaneously have a positive and significant effect on Purchasing Decisions.